A prospective, randomized, controlled, double-blind, multi-center study to evaluate the efficacy and safety of a blue light device for the treatment of chronic back pain - Baron, Ralf; Morlion, Bart; Dahan, Albert; Überall, Michael; von Basum, Golo; Wild, Imane (Frontiers in Pain Research, 2024)
IntroductionChronic back pain is one of the most prevalent conditions and has a large socio-economic impact. The lack of routine use of non-pharmacological options and issues associated with pharmacological treatments underscore high unmet needs in the treatment of back pain. Although blue light phototherapy has proven efficacy in dermatology, limited information is available about its use in back pain.MethodsIn this proof-of-concept, randomized controlled trial, a pain relief patch (PRP) delivered blue light at the site of back pain for 30 min during five treatment sessions. The comparator device delivered green light for 5 s but was worn for 30 min. A follow-up visit took place after the last treatment. The primary objective was to demonstrate the superiority of treatment by PRP, compared to the control device, in reducing pain intensity at the end of the treatment period. The post-treatment visual analog scale (VAS) pain intensity score for each group was calculated across the five treatment sessions and compared to the baseline. Secondary objectives included the disability score (Roland–Morris Disability Questionnaire) and safety.ResultsThe full analysis set included 171 patients. A statistically significant reduction in pain intensity occurred after the use of PRP (p < 0.02), but the study did not meet its primary objective of a superiority trial aimed at demonstrating a 0.6 cm difference in favor of PRP on the VAS scale. There was no significant change in the disability scores. Subgroup analyses were performed to identify the treatment response by patient characteristics such as pain intensity at baseline and skin type. As expected, safety data showed erythema and skin discoloration in the PRP group but not in the control group.Discussion/conclusionThis trial had multiple limitations that need to be addressed in future research. Although the primary objective was not achieved, this proof-of-concept study provides important efficacy and safety data in relation to the use of blue light in the treatment of chronic back pain and key insights that may support further research on similar devices.Clinical Trial RegistrationClinicalTrials.gov, identifier NCT01528332.